Perbandingan Sistem Pendidikan Tinggi Program Sarjana di Australia dan Inggris - Achmad, Novianita; Panai, Abdul Haris; Mas, Sitti Roskina; Zulystiawati, Zulystiawati (Research in the Mathematical and Natural Sciences, 2024)
Higher education in Australia and the UK has undergone significant transformation in recent decades, facing challenges of inclusion, representation and efficiency. In Australia, significant changes have occurred in higher education funding, moving to a more flexible and performance-based model, while the UK still struggles with issues of elitism and social inequality. Both countries face challenges in learning mathematics related to infrastructure and understanding complex concepts. However, both offer strong learning experiences that are relevant to industry needs. This research aims to compare the two countries' higher education systems and analyze the factors that influence the quality of their education, using a descriptive method with diverse data sources such as official reports, academic research and statistical data. The results show that Australia has successfully improved accessibility and equity through diversification and scholarship programs, while the UK still faces major challenges in inclusion and representation. The findings offer important insights into how both countries face the challenges of higher education and seek to develop more inclusive and efficient systems. This research can serve as a reference for governments and educational institutions in developing more effective education policies, capitalizing on Australia's success in diversification and accessibility, and overcoming the obstacles faced by the UK in its efforts to achieve inclusion and social equity in higher education.